COMPARATIVE CHARACTERISTICS OF REGIONAL FEATURES OF AVERAGE VALUES OF SP AND DP IN AGE AND ETHNOSEXUAL ASPECT - I. O. Vologdina (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
4615 children have been screened: 2410 [52.2 %] are Russians, and 2205 [47.8 %] are Buryats; 2159 [46,8 %] of them are boys, and2454 [53,2 %] are girls. The widely spread risk factors of arterial hypertension development are heritable heart diseases, smoking (including passive smoking), overweight, as well as a sedentary way of life in different sex, age and ethnic groups. The results of the screening showed that the hypodynamia are more typical for city-dwellers, than for villagers. It is proved that high blood pressure prevalence is dependent on the phase of sexual development of girls belonging to both ethnic groups.